Minding the gap in pediatric headache care: Can a focus on quality measures improve outcomes?. Issue 3 (June 2019) - Turner, Scott; Foss-Barratt, Amanda; Malmberg, Jessica; Disabato, Jennifer
Abstract : Background: The American Academy of Neurology Headache Quality Measures seek to improve care delivery and outcomes by addressing gaps in care. Our practice identified underperformance in 3 of the 7 measures that apply to children and adolescents. We expected that improved performance on these measures would lead to a reduction in emergency department (ED) visits and improvement in the average disability grade of established patients. Methods: An interdisciplinary workgroup used the Institute for Healthcare Improvement's Model for Improvement. Quality improvement (QI) interventions focused on the use of Pediatric Migraine Disability Assessment (PedMIDAS), headache action plans (HAPs), nurse triage, and infusion center order sets. Results: Provider use of PedMIDAS increased from 15% to 55% ( p <0 .0001) of patient visits during the comparison period. Generation of HAP letters increased from 10% to 15% ( p < 0.0003), but these gains were not sustained. ED visits for headache decreased by 32% ( p < 0.0001). The average migraine disability grade remained unchanged. Conclusions: QI efforts using team-based strategies and electronic medical record (EMR) integration can improve performance on headache quality measures, although it may be difficult to demonstrate improved patient outcomes. The project's time frame and disability assessment strategy were likely insufficient to detect a change in disability. Optimization of nurse triage and EMR workflows enabled more patients with status migrainosus to receive their treatment in the infusion center rather than the ED with a favorable revenue benefit for the hospital.